EFFECT OF INCUBATION TIME AND CHICKEN MANURE Tricoderma Harzianum DIRT IN PEAT SOIL FOR GROWTH AND YIELD OF PERENGGI CHILI PLANTS - gunawan, huda (Jurnal Sains Pertanian Equator, 2014)
The purpose of this research to know the exact incubation time for growth and yield of perenggi chili plants in peat soil, given Trichoderma harzianum mean while another was not. The research plan used is factorial completely randomized design (CRD) consist of 2 factors. The fist factor were incubation time of chicken manure fertilizer (t) through 3 lever of actions. t1 = incubation time were two weeks (2), t2= incubation time were three weeks (3), t3 = incubation time were four weeks and the second factor was aplication of Tricoderma harzianum (W) using four levels of action. w0 = without Tricoderma harzianum,w1 = Tricoderma harzianum of 20 ml/liter concentration, w2 = with Tricoderma harzianum of 40 ml/liter concentration, w3 = Tricoderma harzianum of 60 ml/liter of water concentration. There are 12 combinations of actions repeated 3 times and there are 3 sample of plants. The variables observed in this research were plant height, leaf chlorophyll content, plant dry weight, root volume, blossom time, amount of fruits for each tree, weight of fruits for each tree, acidity, tempereture, rainfall, and humidity in the field. The research result shows that the effect of incubation time and application of Trichorderma harzianum make no differences to the growth and yield of chilli perenggi in peat moss soil. The effective dose of Trichoderma harzianum to improve the growth and yield of chilli perenggi in peat soil is concentration of 40 ml/liter and there was no interaction. Between incubation time and concertration of Trichorderma harzianum to the growth and production chilli perenggi. Keyword : Peat moss soil, Chilli perenggi, Tricoderma harzianum, Chicken manure.